Analysis of Risk Factors for 24 Patients With COVID-19 Developing From Moderate to Severe Condition - Li, Dianming; Liu, Chuanmiao; Liu, Jiahui; Hu, Junfeng; Yang, Yanli; Zhou, Yufu (Frontiers in Cellular and Infection Microbiology, 2020)
Objective: The present study aimed at investigating the clinical risk factors for COVID-19 patients developing from moderate condition to severe condition, and providing reference for early intervention and prognosis. Methods: We collected the clinical data of 24 patients with moderate-to-severe COVID-19, comparing with the clinical data of 41 patients with moderate condition in the same period, thus summarized the current knowledge of potential risk factors for COVID-19 patients developing from moderate to severe condition. Results:(1) The moderate-to-severe group and the moderate group in terms of combined underlying diseases and respiratory frequency showed significant difference statistically (P<0.05), while no significant difference between the two groups in gender, age and clinical symptoms was statistically observed(P >0.05). (2) The lymphocyte count and plasma albumin of the moderate-to-severe group were significantly lower than those of the moderate group (P < 0.05), and the blood glucose and urea of moderate-to-severe group were significantly higher than those of the moderate group (P < 0.05). However, there was no significant difference in terms of white WBC, PLT and GPT (P>0.05). (3) The level of IL-6 and CRP of moderate-to-severe group were significantly higher than those of the moderate group (P <0.05). (4) As for patients with moderate COVID-19, In chest imaging, the more obvious the change of ground glass shadow or flake shadow or lung consolidation is, the more likely it is to evolve to severe type，and the differences were statistically significant (P < 0.05). Conclusion: Current evidence suggested that the combination of underlying diseases, respiratory frequency, lymphocyte count, blood glucose, albumin, urea level, inflammatory factors (CRP, IL-6) and imaging manifestations collectively contributed to the potential risk factors for the development of COVID-19 from moderate condition to severe condition. Particular attention should be paid to early detection which will be of vital significance to the ascent of the recovery rate as well as the reduction of mortality.